2002
DOI: 10.1046/j.1365-2036.16.s2.5.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between gastric cancer cells circulating in the blood and microsatellite instability positive gastric carcinomas

Abstract: Background: Cancers characterized by microsatellite instability may be biologically different from their counterparts with stable microsatellite sequences. Circulating cancers cell present in blood prior to surgery may constitute an adverse prognostic finding. Aim: To correlate these two phenomena with morphological features and survival in advanced gastric cancer. Methods: We examined 76 cases of resected sporadic, advanced gastric cancer by means of routine morphology and a panel of microsatellite markers. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 20 publications
(51 reference statements)
0
18
0
Order By: Relevance
“…Characteristics of the included studies are presented in Supplement Table SI [48], Poland (1) [44], Spain (1) [41], Australia (1) [38], Germany (1) [37], Portugal (1) [36], and the UK (1) [35]]. Only three studies [54][55][56] enrolled patients during the 21st century, and all studies analyzed patients with stage I-IV gastric cancer, with the exception of two studies (one study [35] included stage I-III, and one study [45] did not provide information on stage).…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Characteristics of the included studies are presented in Supplement Table SI [48], Poland (1) [44], Spain (1) [41], Australia (1) [38], Germany (1) [37], Portugal (1) [36], and the UK (1) [35]]. Only three studies [54][55][56] enrolled patients during the 21st century, and all studies analyzed patients with stage I-IV gastric cancer, with the exception of two studies (one study [35] included stage I-III, and one study [45] did not provide information on stage).…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…The number of markers used to estimate MSI status ranged from one to eleven, and a diversity of thresholds for assigning MSI-H or MSI was applied among the studies. Thirteen studies [7,36,37,[39][40][41]43,47,49,51,[54][55][56] used a combination of mono-and dinucleotide markers, seven [6,38,42,44,45,50,52] used only mononucleotide markers, and three [35,48,53] used only dinucleotide markers. In two studies [38,45], only one mononucleotides marker, BAT26, was used for estimating MSI status, and one study [46] considered hMLH1-negative cases MSI-H. Only four studies [49,[54][55][56] followed the National Cancer Institute (NCI) guidelines for the determination of MSI in colorectal cancer [58] (i.e., two mononucleotide markers [BAT25 and BAT26] and three dinucleotide markers [D5S346, D2S123, and D17S250]).…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…This is in agreement with other reports published in the literature, 54,55 although some studies have found no statistical association between tumor site and MSI-H phenotypes. 50,51,56 Females were found to have MSI-H tumors more frequently than males. Most studies have not reported a gender difference associated with MSI-H status, 41,50,51,55 although the data published by Olivera and colleagues, 54 Ohmura and colleagues, 42 and Ottini and colleagues 43 seems to show a similar trend to what we have observed.…”
Section: Discussionmentioning
confidence: 99%